The Influence of Transparency and Accountability on the Effectiveness of Village Revenue and Expenditure Budget Governance (APBDes) to Achieve Good Governance in Villages of Wonoayu District, Sidoarjo Regency. - Abdhilla, Indhira Ridho; Narastri , Maulidah (Business and Investment Review, 2025)
This study aims to determine the effect of transparency and accountability on the effectiveness of APBDes governance in the villages of Wonoayu District, Sidoarjo Regency. This study uses descriptive quantitative methods. This study revealed that transparency has a positive and significant impact on the effectiveness of APBDes governance in the Wonoayu District villages. It highlights that transparency facilitates better budget disclosure and enhances public understanding of financial management processes. Conversely, accountability showed no significant effect on APBDes governance effectiveness, indicating the need for additional support such as external oversight and community participation. Collectively, transparency and accountability simultaneously have a significant influence, emphasizing the critical role of open and collaborative financial management in achieving good governance.conclusion: This study concludes that transparency plays a crucial role in enhancing the effectiveness of APBDes governance. Transparency ensures the disclosure of budget information to the public, fostering trust and participation in village financial management. However, accountability alone does not significantly impact governance effectiveness, suggesting the necessity of additional mechanisms, such as external monitoring and active community involvement, to optimize its influence. Collectively, transparency and accountability positively and significantly contribute to strengthening APBDes governance. These findings underline the importance of fostering transparency and reinforcing accountability to achieve good governance principles at the village level.